PERFORMANCE ANALYSIS OF REGIONAL GOVERNMENT OWNED ENTERPRISES BANK PERKREDITAN RAKYAT MAJATAMA AND THE REGIONAL WATER SUPPLY COMPANY OF THE MOJOKERTO REGENCY GOVERNMENT IN FINANCIAL PERSPECTIVE - -, Kariyoto (The International Journal of Accounting and Business Society, 2020)
Purpose — The purpose of this study is to evaluate the performance of the Mojokerto Regency 2019 Regional Owned Enterprises (BUMD).Design/methodology/approach — The research method used is descriptive qualitative analysis. The stages of preparatory research determine the techniques used in the analysis. The next stage gathers indicators in measuring financial performance. Determine the criteria in accordance with the theory used for financial performance analysis. Collection and analysis of financial data of BPR Majatama and the Regional Water Company.Findings — The results of the study show that Majatama People's Credit Bank Study of the Gross Value of Bad Debt in July, August, September, and October 2019 are safe.Originality/value — This study evaluates the performance of the People's Credit Bank Majatama. It also evaluates the performance of the Regional Water Supply Company and provides performance recommendations.Practical Implication — The calculation of Gross and Net non-performing loans experiences a positive trend and is far from the maximum limit required by Bank Indonesia of 5%. Regional Water Supply Companies in July, August, September, and October 2019, management is advised to control the general administrative costs, increase revenue and reduce operating costs through efficiency and effectiveness to increase profits in the following month.Research Type Research PaperKeywords Performance, Regional-Owned Enterprises, Majatama Rural Credit Banks, and Regional Water Companies.